KEHIDUPAN SOSIAL EKONOMI PEMULUNG DI TEMPAT PEMBUANGAN AKHIR (TPA) RABERAS KELURAHAN SEKETENG KECAMATAN SUMBAWA KABUPATEN SUMBAWA - Ramlafatma, Ramlafatma (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Scavengers are social groups who have a business to collect used goods. The job of scavengers is often seen as trivial by some people because it is close to a dirty environment and low income results. The life of scavengers from a social perspective is often underestimated by some because they are considered dirty, close to disease and provide low income. Regarding the socio-economic conditions of scavengers, they are identified with poverty. From the background above, the author wants to explore how the socio-economic life of the scavengers in TPA Raberas, Seketeng Village, Sumbawan District, Sumbawa Regency. The purpose of this study was to find out the background of the life of scavengers at the TPA Raberas, to find out what factors influenced the scavengers to continue working as scavengers at the TPA Raberas and to find out how the level of awareness of the surrounding community towards the scavengers at the TPA Raberas. The method used in this research is descriptive qualitative data in the form of words that describe symptoms, facts or events systematically and accurately. Socially, people who work as scavengers are people who come from very poor groups with very weak economic conditions, forcing them to work as scavengers who have to be at the final disposal site every day to collect used goods which they can turn into rupiah. to keep them alive. Economically, they are in very poor condition. Factors that influence people who work as scavengers include educational, economic and social factors.